THE EFFECTIVENESS OF ANTI-CORRUPTION EDUCATION COMMUNICATIONS IN ISLAMIC RELIGIOUS EDUCATION AND ITS IMPLEMENTATION IN LEARNING - Muhtadin Muhtadin (Moestopo International Review on Social, Humanities, and Sciences, 2021)
The background of this research is an attempted to participate in education for eradicating the corruption behavior. In this attempted, it is necessary to inculcate anti-corruption values​ that are integrated into existing subjects, so they are not burdensome to emerge new subjects. Furthermore, to provide this education, an effective learning process is needed by using the right communication process so that the cultivation of anti-corruption values ​​can be implemented optimally. This study aims to reveal the anti-corruption values ​​contained in Islamic Education textbooks and then provide an overview of how to build effective communication to be used in learning. This research is a library research with student textbooks as the object of study. The results showed: the values ​​of anti-corruption education contained in the textbook of Islamic Religious Education and Character are the values ​​of honesty, caring, independence, discipline, responsibility, hard work, simplicity, courage, and justice. Effective communication occurs when paying attention to at least five things: clarity of material, accuracy of language use, material context, communication flow, and the environmental culture of students.